2020
DOI: 10.1103/physrevlett.124.188002
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of Entangled Active Polymer-Like T. Tubifex Worms

Abstract: We experimentally study the rheology of long, slender, and entangled living worms (Tubifex Tubifex). Their level of activity can be controlled by changing the temperature or by adding small amounts of alcohol to make the worms temporarily inactive. Performing classical rheology experiments on this entangled polymer-like system, we find that the rheology is qualitatively similar to that of usual polymers, but, quantitatively, (i) shear thinning is reduced by activity, (ii) the characteristic shear rate for the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 53 publications
1
47
0
Order By: Relevance
“…The T. tubifex worms that we investigate are active swimmers and approximately 300 μm thick and 10-40 mm long (see Supplemental Material [21]). The thermal random motion of the worms (estimated from the Stokes-Einstein equation) is negligible compared to their active motion, so they constitute a good model system for active polymers [25][26][27][28][29][30]. When randomly distributed over a volume of water, the worms aggregate spontaneously (Fig.…”
mentioning
confidence: 99%
“…The T. tubifex worms that we investigate are active swimmers and approximately 300 μm thick and 10-40 mm long (see Supplemental Material [21]). The thermal random motion of the worms (estimated from the Stokes-Einstein equation) is negligible compared to their active motion, so they constitute a good model system for active polymers [25][26][27][28][29][30]. When randomly distributed over a volume of water, the worms aggregate spontaneously (Fig.…”
mentioning
confidence: 99%
“…Condensed active matter is defined as an ensemble of constituents that consume energy to do mechanical work while remaining entangled or in physical contact with one another (Hu et al, 2016). Examples of such systems are omnipresent in nature and include systems ranging from the cytoskeletal walls of single cells (Neuhaus et al, 1983) to clustered aggregations of worms or insects (Adams et al, 2011; Deblais et al, 2020; Peleg et al, 2018). This material class is exemplary for its ability to display complex cooperative behavior and morph despite remaining cohesively unified.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by these experiments and insights on aggregations of blackworms and sludge worms [17,23,16], we pursue a theoretical model that captures the collective behavior of aquatic worms by linking together local rules governing interactions between individual worms with the emergent macroscale dynamics of the blob.…”
Section: Introductionmentioning
confidence: 99%
“…Other recent work has investigated the rheology and phase separation in aggregations of a similar organism, Tubifex tubifex , also called the sludge worm or sewage worm. These worms also form highly entangled blobs in water to minimize exposure to poisonous dissolved oxygen, though collective locomotion has not been observed [23, 16]. It was shown that modeling the aggregation of small worm blobs into larger blobs as the coalescence of droplets undergoing Brownian motion was insufficient to capture the dynamics observed in the experiments [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation